The best factors that influence training effectiveness / Muna Zaleha Che Ismail...[et al.] - Che Ismail, Muna Zaleha; Che Ismail, Che Farah; Zakaria, Shakirah (2010)
The title of this research is a study in determining the factor that influences training effectiveness among staff in UiTM Kedah. The research objectives are to identify whether self efficacy gives influence to effectiveness of training, to know whether the training can make an individual or group of people more productive, efficient and useful to organization, to identify whether training boost up the staff self motivation, and also to investigate the factors that influencing training among non-academic staff in UiTM Kedah. Total respondents of 60 staffs in UiTM Kedah to fill the set of questionnaire that consists of sections which are demographic data (Section A), training needs towards employees (Section B), training motivation (section C), and training program design (Section D). This research used quantitative method. The result indicates that self efficacy is the best factor that influences training effectiveness.